1974
DOI: 10.1007/bf00017944
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of chromium-51 in lowland rice in relation to the chemical form and to the amount of stable chromium in the nutrient solution

Abstract: Distribution of radiochromium at the plant and cellular levels varies with the chemical form added to the nutrient medium. Cr EDTA is less absorbed and metabolized by the roots than Cr +++ and CrO4--but its translocation rate is clearly higher.More than 99 percent of the Cr +++ and CrO4--absorbed remained bound in the roots and in the concentration range used absorption was proportional to the nutrient solution content.Protoplasmic fractions of roots contained the highest percentage of Cr +++ and CrO4--activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

1979
1979
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 11 publications
1
10
0
1
Order By: Relevance
“…Chromium concentrations in roots and shoots of CrO 2À 4 -supplied plants averaged 170 and 1.7 mg Cr Kg À1 DW, respectively, while those of Cr 3 -supplied plants averaged 110 and 1.1 mg Kg À1 DW, respectively. These results con®rm those obtained earlier by other researchers (Human and Allaway 1973;Myttenaere and Mousny 1974;Lahouti and Peterson 1979;Parr and Taylor 1980). The restriction in the translocation of both Cr forms in plants to the same degree, despite the dierential accumulation in roots and shoots, suggests that interconversion between CrO 2À 4 and Cr 3 is almost certain to occur in roots.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Chromium concentrations in roots and shoots of CrO 2À 4 -supplied plants averaged 170 and 1.7 mg Cr Kg À1 DW, respectively, while those of Cr 3 -supplied plants averaged 110 and 1.1 mg Kg À1 DW, respectively. These results con®rm those obtained earlier by other researchers (Human and Allaway 1973;Myttenaere and Mousny 1974;Lahouti and Peterson 1979;Parr and Taylor 1980). The restriction in the translocation of both Cr forms in plants to the same degree, despite the dierential accumulation in roots and shoots, suggests that interconversion between CrO 2À 4 and Cr 3 is almost certain to occur in roots.…”
Section: Discussionsupporting
confidence: 93%
“…Supporting evidence for this hypothesis comes from Cr uptake studies when Cr was supplied in chelated forms. A marked enhancement in the translocation of Cr to plant tops was observed when CrEDTA, which is not retained by ion exchange, was supplied as compared to the ionic forms of Cr (Myttenaere and Mousny 1974;Athalye et al 1995;Cary et al 1977). In addition, Skengton et al (1976) illustrated that Cr 3 and CrO 2À 4 enter the vascular tissue with diculty; however, once in the xylem, Cr moves more readily.…”
Section: Discussionmentioning
confidence: 93%
“…This was explained by the propensity of Cr(III) to bind to cell walls, as Cr(III) was the predominant species detected in roots (Zayed et al, 1998). A marked enhancement in the translocation of Cr to aerial plant organs was observed when Cr(III)-EDTA was supplied as compared to ionic forms of Cr (Myttenaere and Mousny, 1974;Athalye et al, 1995;Srivastava et al, 1999). Thus, Cr(III) uptake showed similar features as Fe(III) uptake, which gave rise to investigate the interaction of both elements in plants.…”
Section: Introductionmentioning
confidence: 87%
“…It has been reported that after uptake of Cr(IV), it is Fig. 1 The overview of chromium resources and uptake responses in plants immediately reduced to Cr(III) in the cells (Myttenaere and Mousny 1974). Cr(III) is located in the cytosol inside the cell (Yamamoto et al 1981).The persistence of Cr in soil can lead to increase in the uptake by the plants and the persistence is due to low mobility and recalcitrant nature of the metal.…”
Section: Chromium Uptake Transport and Distribution In Plantsmentioning
confidence: 97%